ANALISIS DISCOUNT PRICE TERHADAP OCCUPANCY RATE PADA HOTEL LAMPANG PALANGKA RAYA - Sri Hartini (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2019)
This research aims to determine the influences of Discount Price on Occupancy Rate applied by Lampang Hotel Palangka Raya city. It is used research method by Comperative method and Simple Regression analysis in order to determine the influences of Discount Price strategy on Occupancy Rate whether it can increase or decrease on Lampang Hotel Palangka Raya City.Results of the Discount Price strategy on Occupancy Rate are seen as the strategy that can be used by the Hotel Management to determine comparison of each room type to be rented by guests. Therefore, it indicates percentage of room renting realization on Sahid Hotel namely for standard rooms, there is 100% renting realization, for standard room, there is 99,97%.And for business, the rental realization is 99.94% so that the application of Discount Price can increase the Occupancy Rate in Lampang Hotel Palangka Raya City with an increase in percentage for STD, DLX, and BIS types on average is above 50%.From results of these calculations, it can be obtained simple regression as follows: Y = -0,258 + -1,628x. This shows that Discount Price or X is directly proportional to Occupancy Rate or Y. If the Discount Price increases, the Occupancy Rate also increases, otherwise, if the Discount Price decreases the Occupancy Rate will also decrease.